Analysis of the Competitiveness of Teak Wood Export in Togo (West Africa) - Gatonnou, Komla Mensah; Kokutse, Adzo Dzifa; Kokou, Kouami; Koffi-Tessio, Egnonto M.; D. Agbodji, Akoété Ega (European Scientific Journal, ESJ, 2017)
The log export ban in favor of value-added wood products remains a challenge for developing countries in the context of maximizing national income from international timber trade at the expense of sustainable forest management. This study attempts to shed light on this subject matter through an analysis of the competitiveness of teak wood in Togo. The policy analysis matrix was developed using teak exporter budgets with reference to national and international market prices collected in July and August 2014. The results show that Togo has no comparative advantage in the squared teak trade which is the result of processing teak in Togo, whatever the level of price observed during this period. On the other hand, it is better for Togo to sell its log on the international market when the price reached 542 USD/m3 (maximal price observed). Togo does not sufficiently protect its national market to maximize income for exporters.